Postcolonial Pragmatics: Changing lenses - Rocha Azevedo, Dora Savoldi da (Revista da ABRALIN, 2020)
Seeking to account for the specificities of interactions in postcolonial societies contexts, Eric Anchimbe and Richard Janney (2010) developed the Postcolonial Pragmatics framework, which was the topic of Anchimbe’s homonymous lecture in Abralin ao vivo. As a result of colonization and the consequent mixture between indigenous and colonizers ways of life, postcolonial settings are marked by hybridized forms of concepts, language, social norms, and speech (e.g. code-mixing and code-switching), thus leading to communication strategies which have been shaped by these heterogeneous environments. Postcolonial Pragmatics consists of a framework based on an emic perspective which aims at taking into account the hybrid settings found in postcolonial societies in pragmatic analysis. Anchimbe presents us with a new theoretical lens through which phenomena drawn from these hybrid settings are considered central to the Pragmatics’ enterprise.